Treatment of Ruptured Abdominal Aortic Aneurysms: State of the Art - Oliveira-Pinto, José (2018)
Introduction: Endovascular aneurysm repair for ruptured abdominal aortic aneurysm has been increasingly advocated due to short term benefits. Most observational studies point towards survival advantage for endovascular aneurysm repair over open repair. However, randomized clinical trials already performed did not support this data. The aim of this review is to compare post-operative outcomes between endovascular aneurysm repair and open surgery for the treatment of ruptured abdominal aortic aneurysms.Materials and Methods: MEDLINE databases were searched to access outcomes after endovascular aneurysm repair for ruptured abdominal aortic aneurysm and open repair for ruptured abdominal aneurysm repair. All the randomized controlled trials were included. Large and contemporary observational studies were also considered.Results: Thirty day mortality ranged between 18% - 53% for endovascular aneurysm repair for ruptured abdominal aortic aneurysm and between 24% - 53% for open repair. Post-operative complications ranged between 33% - 77% for endovascular aneurysm repair for ruptured abdominal aortic aneurysm and 37% - 80% for open repair. In hospital stay ranged between 8.5 and 14.3 days for endovascular aneurysm repair for ruptured abdominal aortic aneurysm and between 12.2 and 20.5 days for open repair. Intensive care unit days ranged between 1.75 - 4.2 days for endovascular aneurysm repair for ruptured abdominal aortic aneurysm and 2.5 - 6.3 days for open repair.Discussion: Survival benefit is found for endovascular aneurysm repair for ruptured abdominal aortic aneurysm in most observational studies, but those are not reproduced by randomized controlled trials data. However, endovascular aneurysm repair for ruptured abdominal aortic aneurysm showed less post-operative complications and hospitalization days.Conclusion: Endovascular aneurysm repair for ruptured abdominal aortic aneurysm should be considered as first line of treatment in centers with expertise and proper facilities.